Adaptation of the basic resuscitation skills self-efficacy scale in nursing students to Turkish : a validity and reliability study - Gules, Halil Ibrahim; Dag, Gulten Sucu (Bmc, 2025)
BackgroundNurses' resuscitation self-efficacy levels are a key component in the acquisition of basic resuscitation skills. However, there is no measurement tool to determine nursing students' resuscitation self-efficacy in our country. This study was conducted to adapt in the nursing students the Basic Resuscitation Skills Self-Efficacy scale to Turkish and determine its validity and reliability.MethodsA descriptive, cross-sectional, and methodological design was used. The study was conducted with nursing students from two universities in Northern Cyprus between August 2023 and November 2023. The study included 605, second, third, and fourth-year nursing students. The data were collected using descriptive characteristics form and the basic resuscitation skills self-efficacy scale.ResultsThe scale showed a 2-factor structure, namely CPR and OED use, Casualty Recognition and Safety and consisted of 18 items. In confirmatory analysis, all factor loads were found to be between 0.50 and 0.87. The fit indexes of the inventory were chi 2/df = 3.647, GFI = 0.906, NFI = 0.908, CFI = 0.921, RMSEA = 0.079. Cronbach's alpha of the total scale was 0.887.ConclusionsThe Turkish version of the Basic Resuscitation Skills Self-Efficacy Scale was valid and reliable and could be used to determine the students resuscitation self-efficacy.
Keywords: Basic resuscitation skills; Self-Efficacy; Nursing students; Validity; Reliability